Welding and joining of magnesium alloys - Liming, Liu (Woodhead Publishing in materials., 2010)
Due to the wide application of magnesium alloys in metals manufacturing, it is very important to employ a reliable method of joining these reactive metals together and to other alloys. Welding and joining of magnesium alloys provides a detailed review of both established and new techniques for magnesium alloy welding and their characteristics, limitations and applications. Part one covers general issues in magnesium welding and joining, such as welding materials, metallurgy and the joining of magnesium alloys to other metals such as aluminium and steel. The corrosion and protection of magnesium alloy welds are also discussed. In part two particular welding and joining techniques are reviewed, with chapters covering such topics as inert gas welding, metal inert gas welding and laser welding, as well as soldering, mechanical joining and adhesive bonding. The application of newer techniques to magnesium alloys, such as hybrid laser-arc welding, activating flux tungsten inert gas welding and friction stir, is also discussed. With its distinguished editor and expert team of contributors, Welding and joining of magnesium alloys is a comprehensive reference for producers of primary magnesium and those using magnesium alloys in the welding, automotive and other such industries, as well as academic researchers in metallurgy and materials science. Provides a detailed review of both established and new techniques for magnesium alloys welding and their characteristics, limitations and applicationsBoth the weldability of magnesium alloys and weldability to other metals is assessed as well as the preparation required for welding featuring surface treatmentParticular welding and joining technologies are explored in detail with particular chapters examining hybrid laser-arc welding, laser welding and resistance spot welding.